2020
DOI: 10.1097/md.0000000000022429
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-behavioural reflective training for improving critical thinking disposition of nursing students

Abstract: Background/Objective: The importance of critical thinking in improving treatment practices in, for instance, the nursing profession, cannot be overemphasized. Despite this importance, empirical studies have shown that helping strategies to train learners on critical thinking disposition are needed. Given this knowledge gap, this study investigated the impacts of cognitive-behavioral reflective training for improving the critical thinking disposition of nursing students. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Virtual clinical enhanced the self-reflection abilities among students, as they were able to identify their areas of improvement after each activity and showed improved performance in the consecutive virtual and face-to-face interactions with the patients. Our findings were consistent with earlier studies on university students that revealed reflective activities enhances students’ in-depth self-perception and critical thinking which enables them to identify sources and ways of problem solving in their profession ( Abiogu et al, 2020 ; Bubnys, 2019 ; Van Rensburg et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Virtual clinical enhanced the self-reflection abilities among students, as they were able to identify their areas of improvement after each activity and showed improved performance in the consecutive virtual and face-to-face interactions with the patients. Our findings were consistent with earlier studies on university students that revealed reflective activities enhances students’ in-depth self-perception and critical thinking which enables them to identify sources and ways of problem solving in their profession ( Abiogu et al, 2020 ; Bubnys, 2019 ; Van Rensburg et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…In a related study, Malhotra et al (2012) indicated that the existence of a child with disability negatively affects family relationship and wellness. Such negative attitudes and perceptions could be resolved using a well-promising cognitive behavioural treatment (Abiogu et al, 2020a(Abiogu et al, , 2020bAgah et 2020;Agah et al, 2021;Ugwuanyi, et al, 2020aUgwuanyi, et al, , 2020bUgwuanyi, et al, , 2020c like family health-model of REBT among family members to enable them to live up to expectation.…”
Section: Discussionmentioning
confidence: 99%
“…RCT sought to measure and compare the outcomes after the participants receive the interventions. This study design has been used by Nwokeoma et al, [ 8 ] Ogbuanya et al, [ 24 , 25 ] Garfield, [ 26 ] Ugwuanyi et al, [ 36 , 37 , 40 , 42 ] Ede et al, [ 38 ] Agboeze et al, [ 39 ] Okide et al, [ 41 ] Abiogu et al, [ 43 ] and Umoke et al [ 44 ] to carry out similar studies.…”
Section: Methodsmentioning
confidence: 99%